Huso huso ... - Jouladeh-Roudbar, Arash; Ghanavi, Hamid Reza; Doadrio, Ignacio (Zenodo, 2020)
Huso huso (Linnaeus, 1758) – Native (Fig. 26) Acipenser huso Linnaeus [C.] 1758: 238; Type locality: Danube and the rivers of Russia. No types known. Acipenser albula Forster [J. R.] 1767: 354; Type locality: Volga River, Russia. No types known. Acipenser beluga Forster [J. R.] 1767: 354; Type locality: Volga River, Russia. No types known. Acipenser shyp Forster [J. R.] 1767: 353; Type locality: Turkey, Bosphore or Sea of Marmara (Mediterranean Sea). Neotype: NRM 8946. Acipenser schypa Gmelin [J. F.] 1789: 1484; Type locality: Turkey, Bosphore or Sea of Marmara (Mediterranean Sea). Neotype: NRM 8946. Acipenser ichthyocolla Billberg [G. J.] 1833: 52; Type locality: Danube and the rivers of Russia. No types known. Huso ichthyocolla Bonaparte [C. L.] 1846: 22; Unneeded new name for Acipenser huso Linnaeus 1758. Acipenser vallisnerii Molin [R.] 1853: 366, 371; Type locality: Po River, Italy. Acipenser maeoticus Sal’nikov [N. I.] & Malyatskii [S. M.] 1934: 44; Type locality: Sea of Azov. No types known. Huso ... : Published as part of Jouladeh-Roudbar, Arash, Ghanavi, Hamid Reza & Doadrio, Ignacio, 2020, Fig. 4 in Fig. 4 in Fig. 3 in Fig. 21. Sesarmops mora n in Paralbunea dayriti, pp. 1-303 in Zoological Studies 59 (21) on pages 18-19, DOI: 10.6620/ZS.2020.59-21, http://zenodo.org/record/12822787 ...